Cameroon : 2018 Article IV Consultation, Second Review Under the Extended Credit Facility Arrangement Requests for Waivers of Nonobservance of Performance Criteria and Modification of Performance Criteria-Press Release; Staff Report; and Statement by the Executive Director for Cameroon. - International Monetary Fund. African Dept. (Washington, D.C. : International Monetary Fund, 2018)
Cameroon's macroeconomic performance has been mixed against the backdrop of slower economic activity and rising security concerns, with a weaker-than-envisaged fiscal consolidation in 2017. While external buffers are being rebuilt, the CEMAC's recovery remains fragile. Renewed efforts to implement the fiscal consolidation and reform program will be essential to buttress external and fiscal sustainability and reinvigorate growth.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet